Evaluation of Biofertilizer “Myco-green” on Water Relation and Efficiency of Potato Minituber Production in Drought Stress Condition - K. Parvizi; M. Chan (Majallah-i ̒Ulum-i Bāghbānī, 2016)
Introduction Today biological fertilizers are suitable substitutes for chemical manure. Hence they can improve soil fertility in sustainable agriculture system (Mandal et al, 2007). Moreover, in some composition they are accompanied with plant growth promoting rhizibacteria (PGPR), namely Pseudomonas and some Bacillus species. These bacteria can improve growth rate of the plants by some physiological aspects namely, cidrophore acid production, increasing endogenously phytohormone and helping more phosphor absorption and fixation of biological nitrogen (Tilack et al., 2005). The symbiosis of mycorrhiza with plants confers numerous benefits to host plants including improved plant growth and mineral nutrient absorption, tolerance to diseases and stresses such as drought, temperature fluctuation, metal toxicity, salinity and other adverse conditions (Fortin et al, 2002. Ryan et al, (2003) and Smith and Reed, (2008).Mycorrhizal plants are capable of absorbing more water in lower potential of water as compared with non-mycorrhizal plants (Sanchez and Blanco, 2001). Micro propagation of potato by micro and mini tubers have been established for improving multiplication rate and possibility of reserving some more stock plants as germplasm. Multiplication of the minitubers already have been accompanied by lower establishment that causes low vigor and performance of the plant. This experiment was performedto study the effect of biological manure accompanied with mycorrhiza and plant growth promoting rhizobacteria on water relationship and vigor of the plantlets derived from minituber in water stress condition. Material and Methods Myco-green is produced by Peat grow company in Malaysia and has been spreading in floriculture, seed beds, vegetable crops, seedling plant of oil palm and many other plants. The experiment was performedatthe University of International Technology Mara Sarawak (UITM). As first step, soil bed composition was combined with peat and perlite (1:3 ratio). Then it was completely mixed by Mycogreenbiofertilizers by 1 percent of weight ratio. Mixed soil bed and biofertilizer were transferred to boxes. Minitubers of two potato cultivars (Agria and Marfona) were cultivated in the boxes arranged with 6×8 cm distance. The test was conducted in a factorial experiment based on completely randomized design with four replications. The factors included three interval irrigation regimes (5, 8 and 11 days) and two potato cultivars. The amount ofwater supplement according to their treatment was evaluated by weighing the boxes and was calculated as the amount of field capacity base. Fertile grow as a completed micronutrient had been mixed thoroughly in the soil bedby 1% weight proportion because myco-green didnot possess it. Some water relation traits such as leafosmotic potential, relative water content (RWC), osmotic adjustment and leaf proline content were measured. The method described by Bierman and Liderman (10) was used for root colonization assessment. Mini-tuber obtained from any plantlet was weighed, arranged in four groups including less than one gram, between one to three grams, between three to five grams and more than five grams. To assess mini-tuber dry matter of any replication, three mini-tubers were randomly selected and sliced to one mm thick. The first group of samples were weighed-and then placed inside the drying oven for 48 hours at a temperature of 85ºC. The dried samples were weighed again and mini-tuber dry matter percentage was calculated. Two-way analysis of variance (ANOVA) of the data was carried out using SAS software (v. 8.02, SAS Institute, Cary, NC) and the means were compared by the Duncan’s Multiple Range Test. Results and Discussions: Results- showed that application of myco-green biofertilizers had significant effect (p